2011
DOI: 10.1007/s10195-011-0169-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-level anterior cervical discectomy and interbody fusion using PEEK anatomical cervical cage and allograft bone

Abstract: BackgroundIn an effort to avoid the morbidity associated with autogenous bone graft harvesting, cervical cages in combination with allograft bone are used to achieve fusion. The goal of the current study was to assess the reliability and efficacy of anterior cervical discectomy and interbody fusion (ACDF) using a PEEK anatomical cervical cage in the treatment of patients affected by single-level cervical degenerative disease.Methods and materialsTwenty-five patients affected by single-level cervical degenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
31
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 39 publications
12
31
0
6
Order By: Relevance
“…This fusion rate, although not statistically evaluated, is comparable to that reported for single level ACDFs using standalone autografts (97 %) and other allografts (87 %) at 12 months per radiographic evidence [3]. In addition the results compare favorably to fusion rates for other single level ACDF studies using PEEK cages filled with hydroxyapatite (61 and 100 % at 6 and 12 months, respectively) [12], various allografts (100 % at 10-12 months, but not including higher risk patients) [13,14], and carbon fiber reinforced polymer (CFRP) packed with bone marrow-saturated collagen/hydroxyapatite wafers (100 % at 12 months) [20]. In addition, some of these studies [3,14] only used bridging bone as the fusion criteria thus potentially achieving more favorable fusion rates compared to a more stringent criteria.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This fusion rate, although not statistically evaluated, is comparable to that reported for single level ACDFs using standalone autografts (97 %) and other allografts (87 %) at 12 months per radiographic evidence [3]. In addition the results compare favorably to fusion rates for other single level ACDF studies using PEEK cages filled with hydroxyapatite (61 and 100 % at 6 and 12 months, respectively) [12], various allografts (100 % at 10-12 months, but not including higher risk patients) [13,14], and carbon fiber reinforced polymer (CFRP) packed with bone marrow-saturated collagen/hydroxyapatite wafers (100 % at 12 months) [20]. In addition, some of these studies [3,14] only used bridging bone as the fusion criteria thus potentially achieving more favorable fusion rates compared to a more stringent criteria.…”
Section: Discussionsupporting
confidence: 69%
“…When stratifying the 31 patients into high-risk groups it was found that the fusion rates ranging from 70 to 100 % at 6 months to 85-100 % at 12 months were still comparable to the literature where no high-risk patients were included, in particular at 12 months (92-100 %) [10,11,13,14,22]. Having a comparable fusion rates to other PEEK/allograft ACDF studies that have less stringent fusion criteria and do not include a majority of high risk patients indicates that Trinity Evolution may help negate any physiological barrier to fusion during ACDF that is associated with high risk factors.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In spite of that, about 20 % of patients are not completely satisfi ed with the postoperative overall results (11,12) because of persisting diffi culties.…”
mentioning
confidence: 99%